ANALYSIS OF FACTOR INFLUENCING REPURCHASE INTENTION AND WORD OF MOUTH COMMUNICATION MEDIATED BY SATISFACTION - Novita Umi Choirunnisa; Edy Purwo Saputra; Soepatini Soepatini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
In an era of increasingly rapid technological developments, changes and people's needs for practical products are also increasing. One of the most popular food products is Kentucky Fried Chicken (KFC). Therefore, it is important for companies to identify the factors that influence consumer behavior in order to improve the company. This study aims to analyze the factors that influence consumer repurchase intention and word of mouth communication mediated by customer satisfaction at Kentucky Fried Chicken (KFC) companies. Data collection was carried out by providing KCF customer questionnaires with a total of 171 respondents. The statistical analysis used is the Partial Least Square (PLS) based SEM (Structural Equation Modeling) method. The results showed that price fairness, restaurant food quality, and service quality had a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant effect on consumer repurchase intention and word of mouth communication. From the results of this study, it contributes to the KFC company making price fairness, restaurant food quality, service quality a consideration in carrying out marketing strategies related to customer satisfaction and will influence consumer repurchase intention and word of mouth.